Does Providing Clinical Care for Trauma Patients have a Positive Effect on Physicians' Perspective on Child Passenger Safety? - Aykut Çağlar; Figen Çelebi Çelik; Anıl Er; Emel Ulusoy; Utku Karaarslan; Fatma Akgül; Hale Çitlenbik; Başak Bayram; Durgül Yılmaz; Murat Duman (Galenos Yayinevi, 2018)
Introduction: Motor vehicle crashes are the most common cause of the mortality in the pediatric population. Preventive strategies are the best approach to reduce mortality and morbidity due to motor vehicle crashes. Since parents mostly refer to them for guidance, doctors should have a high level of knowledge and awareness to increase the usage of car safety seats. We thought that providing care for trauma patients could have a positive effect on the physicians' awareness and knowledge level. Based on this, we aimed to assess the awareness and knowledge of pediatricians and emergency physicians and trauma doctors. Methods: An electronic survey consisting of 23 questions was prepared. Demographic features, awareness and knowledge level of the physicians were assessed on three sections. Five suggestions in the guideline of the American Academy of Pediatrics were used to assess physicians' knowledge level. The respondents were grouped as those providing clinical care for trauma patients and those do not. Results: The questionnaires were sent to 641 physicians and 323 who completed the questionnaire were included in the study. One hundred and fourteen (35.3%) of the respondents were providing clinical care for trauma patients. One hundred ninety (59.2%) respondents had children. Majority of the physicians had a satisfactory level of knowledge about car safety seat (CSS). The number of respondents reported having adequate self-awareness was found statistically significantly higher in the groups of doctors who have children and provide clinical care for trauma patients (p<0.01 and p=0.01, respectively). However, there was no significant difference in the level of knowledge between non-providers and providers of clinical trauma care (p>0.05). Interestingly, the knowledge level in physicians who had children was statistically significantly lower than in those with no children (p<0.01). Conclusion: Our survey revealed that physicians who provide clinical care for trauma patients think they have a high level of knowledge about CSS. Unfortunately, their knowledge level was low as other physicians in the study group.